The Development of Creative Tourism in China: The Case Studies of Hangzhou, Xiamen and Qingdao - Zeng, Jingyao (2011)
In recent years, the application of creativity has referred to each field including tourism industry. Based on the idea of creativity, creative industry has showed its importance for economic growth. Western countries paid earlier attention to the potential of creativity and creative industry, while developing countries such as China also found out the possibility of usage of creativity. On the other hand, as an extension of cultural tourism, creative tourism adopts creativity into the tourism industry and achieves a new generation of tourism. As an emergent form of tourism, this research examined the potential of development of creative tourism in China. Nottingham city as a successful example was taken to prove its creative arts have played an important role in economy and stimulated creative tourism in the city. Besides, through qualitative interviewing this research gained an insight from potential tourists’ perception and attitudes of creative tourism. It finally through three specific cities Hangzhou, Xiamen and Qingdao exemplified the practical of creative tourism in China. In practice, creative tourism in China can be implemented from aspects including events and creative performance, creative districts and creative activities. In the end, it does show the potential of creative tourism development in China but there is more has to do in the future.